Impact of Microcredit on Poverty Alleviation: Special Reference to Trincomalee District Secretariat Division - Sampavi, M.; Tharshiga, P. (Sri Lanka Finance Association., 2022)
Poverty is the curse upon humanity that leads to human suffering and a state of despair. It has become a huge threat to countries on the margins of globalization. In the Sri Lankan context, poverty is a fundamental question confronted by the government since it negatively affects the development process. The present study has been undertaken to examine the impact of microcredit on poverty alleviation with the objective of assessing how far microcredit influences poverty alleviation. The study was conducted with special reference to the Trincomalee District Secretariat division, which is one of the rural areas where people are in dire financial strains due to the lack of developmental initiatives, resulting in the microcredit institutions invading the area during the last few years. For the study purpose, a sample of 200 microcredit clients was selected using the stratified random sampling technique. The overall findings of the study revealed that there is a statistically significant positive relationship (r=0.701**, p<0.05) between the contribution of microcredit and poverty alleviation. However, interest rate (r=-0.141*) and accessibility of getting the loan (r=0.172*) have a weak relationship with poverty alleviation when compared with loan amount and repayment ability. It was also found that, although loan amount, accessibility of getting loan, repayment ability and interest rate have a significant influence on Poverty Alleviation in Trincomalee, the overall microcredit contribution is at a low level. From the findings of the study, it was suggested that microcredit institutions in Trincomalee should concentrate mainly on the interest rate and the accessibility of loans which will lead to much more effective results. This study can be a base for the studies that are to be extended by considering other suitable dimensions of microcredit contribution and poverty alleviation, and also advisable to extend this study by considering other microfinance institutions in Sri Lanka and other nations too.
Keywords: Microcredit; Loan; Accessibility; Repayment ability; Interest rate; Poverty alleviation